PRELIMINARY-RESULTS OF TRANSURETHRAL MICROWAVE THERMOTHERAPY IN THE TREATMENT OF BENIGN PROSTATIC HYPERPLASIA IN TURKEY - (:unkn) unknown (KARGER, 1992)
This prospective study was conducted in order to evaluate the efficacy of transurethral microwave thermotherapy (TUMT) in the treatment of benign prostatic hyperplasia (BPH). A single TUMT session of 55 min was delivered as an ambulatory procedure without anesthesia to 180 patients. 20 (69%) of the 29 patients who were catheterized due to urinary retention prior to the treatment were able to urinate freely after the treatment. In 91 patients with a follow-up of 3 months, the mean maximum flow rate (MFR) was 7.9 ml/s prior to the treatment and 12.1 ml/s after the treatment (p < 0.02). The mean residual urine after voiding (PVR) of these patients was 104 and 54 ml before and after TUMT, respectively (p = 0.0001). The mean Madsen symptom score (SS) was 14 before and 7.5 after the treatment (p = 0.0001). The patients with pretreatment MFR higher than 7.0 ml/s, PVR less than 150 ml and SS lower than 15 benefited better from TUMT. As the findings indicated, TUMT is an alternative treatment modality in BPH in selected cases, although the number and the follow-up of our series are insufficient to draw a precise conclusion yet.
Keywords: BENIGN PROSTATIC HYPERPLASIA, TREATMENT; TRANSURETHRAL MICROWAVE THERMOTHERAPY; HYPERTHERMIA